Innovative surface, tunnel, and in-pit geophysical methods for mineral exploration and mine planning: case studies from the Bushveld Complex mines, South Africa - Rapetsoa, Moyagabo Kenneth (University of the Witwatersrand, Johannesburg, 2023)
Innovative geophysical methods were used to study the platinum group element mineralisation and their associated geological structures at Maseve and Tharisa mines, western Bushveld Complex. Four case studies are presented in this thesis that incorporate the use of in-mine or near mine geophysical methods for mineral exploration. The first one being in-mine seismic data acquired in 2020 at Maseve mine using cost-effective seismic source and sensors, followed by innovative seismic experiments acquired in 2022 at Maseve mine to evaluate the viability of using tunnel and surface experiments for mineral exploration in a noisy, logistically difficult mine environment. Thirdly, the 2021 integrated geophysical surveys conducted at Tharisa mine to image fractures that act as water pathways into the pit. Finally, integrated geophysical techniques are used to delineate boulders to enhance future mine planning and designs at Tharisa mine. The acquired geophysical data were processed using modern processing algorithms to enhance the target mineralization and complex geological structures in all the sites. In-mine reflection seismic datasets acquired in 2020 at Maseve mine proved useful as they provided optimum imaging of the economic Platinum Group Elements (PGEs) such as the Merensky Reef and Upper Group 2 chromitite layers (known as reefs). This is one of the few in-mine seismic experiments to have been conducted in South Africa for mineral exploration. In 2022, 2D reflection seismic profiles were acquired on surface above the Merensky Reef and Upper Group 2 chromitite, together with four 2D reflection seismic profiles acquired along the mine tunnel at ~ 550 m below the surface and tens of meters above known mineralisation: Merensky Reef and Upper Group 2 chromitite layer. Interpretation of the in-mine and surface seismic data were complemented by the use of 3D ray tracing numerical simulations to understand the distribution and out-of-plane reflectivity from the target mineralization. The 2022 Maseve reflection seismic data improved the imaging of geological structures and mineral deposits. The geophysical data acquired in 2021 at Tharisa mine demonstrated the importance of using near-surface integrated geophysical methods (magnetics, seismics, and electrical resistivity) with other datasets such as borehole logs and physical property measurements to understand the geophysical response of the mineral deposits. Ground magnetic data delineated a major dyke that was identified on the aeromagnetic data and geological mapping. Electrical resistivity tomography, on the other hand, identified linear low resistivity zones that differentiateiii fractured and undisturbed hard rock. Seismic methods were important for depth to bedrock imaging. Integration of geophysical methods was encouraged by the need to understand geological structures (e.g., faults, dykes, iron-rich ultramafic pegmatites, boulders) that can have impact on the efficiency, safety and costs of mining in South Africa. Moreover, this approach encourages the implementation of innovative geophysical surveys in brownfield sites for better mine design and planning, and to increase a life of mine (LoM)
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy In the Faculty of Science to the School of Geosciences University of the Witwatersrand, Johannesburg 2023
Keywords: Mineral explotion; In-mine siesmics; Innovative surface; UCTD; SDG-9: Industry, innovation and infrastructure